Characterization of the atypical Ppz/Hal3 phosphatase system from the pathogenic fungus Cryptococcus neoformans. Issue 4 (18th March 2019) - Zhang, Chunyi; García‐Rodas, Rocío; Molero, Cristina; de Oliveira, Haroldo Cesar; Tabernero, Lydia; Reverter, David; Zaragoza, Oscar; Ariño, Joaquín
Summary: Ppz Ser/Thr protein phosphatases (PPases) are found only in fungi and have been proposed as potential antifungal targets. In Saccharomyces cerevisiae Ppz1 (ScPpz1) is involved in regulation of monovalent cation homeostasis. ScPpz1 is inhibited by two regulatory proteins, Hal3 and Vhs3, which have moonlighting properties, contributing to the formation of an unusual heterotrimeric PPC decarboxylase (PPCDC) complex crucial for CoA biosynthesis. Here we report the functional characterization of CnPpz1 (CNAG_03673) and two possible Hal3‐like proteins, CnHal3a (CNAG_00909) and CnHal3b (CNAG_07348) from the pathogenic fungus Cryptococcus neoformans . Deletion of CnPpz1 or CnHal3b led to phenotypes unrelated to those observed in the equivalent S. cerevisiae mutants, and the CnHal3b‐deficient strain was less virulent. CnPpz1 is a functional PPase and partially replaced endogenous ScPpz1. Both CnHal3a and CnHal3b interact with ScPpz1 and CnPpz1 in vitro but do not inhibit their phosphatase activity. Consistently, when expressed in S. cerevisiae, they poorly reproduced the Ppz1‐regulatory properties of ScHal3. In contrast, both proteins were functional monogenic PPCDCs. The CnHal3b isoform was crystallized and, for the first time, the 3D‐structure of a fungal PPCDC elucidated. Therefore, our work provides the foundations for understanding the regulation and functional role of the Ppz1‐Hal3 system in this important pathogenic fungus. Abstract : We describe the structure and function of CnPpz1 and two putative Ppz1 regulators (CnHal3a and CnHal3b). CnPpz1 is relatively alike to Ppz1 phosphatases in other fungi but is not involved in virulence. CnHal3a and CnHal3b display a function in CoA biosynthesis, but only CnHal3b is important for virulence. Neither CnHal3a and CnHal3b regulate CnPpz1 and, therefore, in contrast to S. cerevisiae and C. albicans, these are not moonlighting proteins.